Establishing a Legal Framework for Sovereign Sukuk Issuance : A Public Debt Management Perspective - World Bank (World Bank, Washington, DC, 2017)
A strong legal framework that forms the basis for the activities of debt managers is crucial for enabling an effective public debt management function. This paper aims to complement discussions on the legal foundations of debt management by detecting and discussing essential elements that allow the government to issue sukuk, the equivalent of bonds, in Islamic finance. Drawing on the cases of recent sovereign issuers, these discussions begin with outlining the clear provision of a mandate to issue and to employ certain public assets in the execution of underlying transactions, as well to establish, engage with, and administer Special Purpose Vehicles used in structuring these issuances. Additional aspects that need to be addressed are the treatment of proceeds and the assurance of investors with regards to debt service. The enabling environment should be complemented by changes in the taxation regime and financial market regulations that facilitate the issuances.